1974
DOI: 10.1017/s000335610001744x
|View full text |Cite
|
Sign up to set email alerts
|

The performance of early-weaned calves offered concentrates or artificially dried grasses

Abstract: In two experiments dried grass cobs or concentrate were offered to calves for 20 weeks after weaning. In Experiment 1 the grasses were harvested in the autumn and in Experiment 2 in the spring. Within each experiment three grasses differing in quality and two levels of concentrate were compared. Dry-matter intake of the dried grasses highest in digestibility was lower than that of medium digestibility grass, and hardness of package, palatability and mould infestation were implicated as possible causal factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1975
1975
1977
1977

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…With increasing dried grass content, since DOM content per kg DM declines linearly, DM requirement increases linearly. Regression analysis of DM requirements against dried grass content indicated a replacement value of dried grass for concentrates of 1*36 : 1, this is similar to the ratio of 1*42 : 1 reported previously (Marsh, 1974). Therefore, within this type of feeding regime it would only be economic to incorporate dried grass into the concentrate pellet when its purchase price is less than 73-5 % of a cereal/protein concentrate on a drymatter basis.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…With increasing dried grass content, since DOM content per kg DM declines linearly, DM requirement increases linearly. Regression analysis of DM requirements against dried grass content indicated a replacement value of dried grass for concentrates of 1*36 : 1, this is similar to the ratio of 1*42 : 1 reported previously (Marsh, 1974). Therefore, within this type of feeding regime it would only be economic to incorporate dried grass into the concentrate pellet when its purchase price is less than 73-5 % of a cereal/protein concentrate on a drymatter basis.…”
Section: Discussionsupporting
confidence: 81%
“…Dried samples of offered feeds were bulked over fortnightly periods, milled and kept for chemical analyses. Moduli of fineness and uniformity of dried grass pellets (E) and of the dried grass meal used in treatments B, C and D, were determined by a process described elsewhere (Marsh, 1974).…”
Section: Experiments 1 2 Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies with artificially-dried grass have also shown that spring-harvested herbage supported greater levels of production from dairy cows (2,6), beef cattle (1) and calves (8,9). Such advantages might not necessarily appear with beef cattle under grazing conditions and any differences that have occurred at pasture could be a result of confounding factors associated with season.…”
Section: Introductionmentioning
confidence: 99%
“…The mean moduli of fineness and uniformity, determined using the method described by Marsh (1974), were 1-0 and 0 : 2 : 8 and the mean density was 1-05 g/ml. The concentrate mixture, which was formulated to have a crude protein content similar to that of the dried grass, contained 69-5 % milled barley, 27-5 % extracted soya bean meal and 3 % minerals and vitamins.…”
Section: Methodsmentioning
confidence: 99%